PERBEDAAN KETERAMPILAN MEMECAHKAN KONFLIK INTERPERSONAL ANTARA SISWA KELAS AKSELERASI DAN SISWA KELAS REGULER DI SMAN RSBI SE-KOTA MALANG - Nawantara, Rosalia Dewi (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTThis study aims to determine differences in interpersonal skills to solve conflicts between acceleration class students and students at SMAN RSBI RSBI class as the city of Malang. This study uses comparative descriptive research design. The subjects were 324 students. Data analysis using t-test to determine differences in interpersonal conflict solving skills among students accelerated classes and regular classes students at SMAN RSBI as the city of Malang. From the results of the t test is known that there are differences in interpersonal skills to solve conflicts between students and regular students acceleration with Sig. 2 tailed 0.003 <0.05. The result of the calculation of standard deviation of acceleration class students by 13, 859, while the standard deviation is lower regular grade students that is equal to 12.579. This suggests that the regular class students have the skills to solve interpersonal conflicts is greater than the acceleration class students, although not significantly. This is supported by the differences in students' social skills, learning time, and location of classes in grade acceleration and RSBI regular class students. Based on the results of these studies can be suggested for counselors accelerated classes to further optimize the guidance and counseling services in the field of social private, so the child can learn to socialize better. For further research is recommended to be able to develop a model of interpersonal conflict resolution skills training, analysis of factors and increase the number of research samples. For the government as policy makers in order to decide back in the right curriculum in lieu RSBI program or try to fix the things that were not appropriate in the curriculum RSBI and then developed into a new, more relevant curriculum. Key Words: Interpersonal Conflict solving skills , Acceleration , Regular , RSBI